The enemies within: Gog of Magog in Ezekiel 38–39 - Lee, Lydia (HTS teologiese studies, 2017)
The most extensive descriptions of Gog and Magog in the Hebrew Bible appear in Ezekiel 38–39. At various stages of their political career, both Reagan and Bush have linked Gog and Magog to the bêtes noires of the USA, identifying them either as the ‘communistic and atheistic’ Russia or the ‘evil’ Iraq. Biblical scholars, however, seek to contextualise Gog of Magog in the historical literary setting of the ancient Israelites. Galambush identifies Gog in Ezekiel as a cipher for Nebuchadnezzar, the Babylonian king, who acted as Judah’s oppressor in the 6th century BCE. More recently, Klein concludes that Gog, along with his companions, is ‘eine Personifikation aller Feinde, die Israel im Buch Ezechiel gegenüberstehen’. Despite their differences in detail, these scholars, such as Reagan and Bush, work with a dualism that considers only the features of Judah’s enemies incorporated into Gog’s characteristics. Via an analysis of the semantic allusions, literary position and early receptions of Ezekiel 38–39, this article argues that Gog and his entourage primarily display literary attributes previously assigned to Judah’s political allies.